Effect of interval training in the pre-competition phase on aerobic capacity and peak power in judo contestants at high sports skill level - Borowiak, W.; Norkowski, H.; Perkowski, K.; Szczucki, W. (Journal of Combat Sports and Martial Arts, 2014)
The aim of the study was to determine the effect of non-specific training stimuli in the form of interval running exercise used during a 5-week training carried out in the pre-competition period on aerobic and anaerobic capacity of judo contestants at high sports skill level. Material and methods. Over twenty five training sessions, 8 judo athletes repeated each time 6 runs at maximum speed (4x14m shuttle run) interspersed with 30-second rest intervals in conditions typical for judo training (barefoot, on a tatami mat). Level of aerobic capacity was determined based on a laboratory exercise test to exhaustion performed on a mechanical treadmill. Level of anaerobic capacity was evaluated based on the results obtained from the Quebec test (10s maximum exercise on cycle ergometer. Results and Conclusions. Comparison between the results obtained during the exercise test to exhaustion and the Quebec test carried out before and after the pre-competition period revealed a statistically significant increase in running speed at the anaerobic threshold (V.AT.), significant increase in mechanical work (J/kg), peak power (W/kg) and elongation of time of maintaining 97.5% peak power in the Quebec test.